Community Participation in Improving The Quality of Education During The Covid-19 Pandemic - Darmawan, I Putu Ayub; Maria, Maria; Mardin, John; Pana, Timoteus Muda (Green Publisher Indonesia, 2022)
This article discusses community participation in improving the quality of education during the pandemic. Researchers used a qualitative approach, with data collection using interviews and observations. The results of the study found several roles of the community in improving the quality of schools, including community involvement in providing guidance to children at home; provide guidance to children in the community, religious leaders, communities, and parents provide supervision and input related to the development of student behavior. Some of the school's efforts in optimizing the role of the community include providing confidence in the community to be involved in quality improvement. Periodic meetings are held to build community involvement. Community involvement also encountered obstacles caused by two factors, namely the lack of public understanding regarding the role of the community and community work factors that caused the low involvement of parents in educating children at home.